2014
DOI: 10.1111/aos.12578
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of the 14F7 Mab raised against N‐Glycolyl GM3 Ganglioside in retinoblastoma tumours

Abstract: ABSTRACT.Introduction: The identification of molecules expressed selectively on the surface of retinoblastoma cells would allow applying targeted therapies. The Ganglioside, N-Glycolyl-GM3 (NeuGc-GM3), is an attractive candidate, as it has been detected in other paediatric neuroectodermic tumours, and it is not expressed in human normal tissues. The 14F7 antibody recognizes specifically the ganglioside NeuGc-GM3. Purpose: To characterize the expression of NeuGc-GM3 in retinoblastoma cell lines and in retinobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
(65 reference statements)
1
21
1
Order By: Relevance
“…New biomarkers for molecular dissemination of retinoblastoma outside the eye may lead to earlier diagnosis of metastasis and targeted treatments. 92,93 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New biomarkers for molecular dissemination of retinoblastoma outside the eye may lead to earlier diagnosis of metastasis and targeted treatments. 92,93 …”
Section: Discussionmentioning
confidence: 99%
“…82,84 However, still too frequently retrospective examination finds a previously unnoticed risk after metastatic disease is diagnosed. Staining of specific markers for photoreceptor cells (the cone-rod homeobox transcription factor; CRX) 92 and for tumour cells (N-glycosylated ganglioside; NeuGc-GM3) 93 may facilitate detection of tumour cells otherwise missed or interpreted as artefact.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…This immunotherapy was designed to induce an immune response against the N-glycolil GM3 ganglioside and it was already tested in phase I study in patients with neuroblastoma 20. We have previously demonstrated that Rb cells showed important amount of this ganglioside 24. Immunotherapy is under consideration for other brain tumours, so we could not rule out the possibility of a contribution of the immune system in limiting intracranial tumour progression in this case 25…”
Section: Discussionmentioning
confidence: 99%
“…Patients in whom CRX was detected in the BM and/or CSF or GD2 synthase was detected in the CSF were considered as having MDD. The CRX mRNA positivity was expressed as relative expression levels according to our previous work . GD2 synthase results were shown as qualitative data (positive‐negative) .…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow (BM) and CSF were collected as part of a prospectively defined schedule-at diagnosis, following induction chemotherapy, and in relapsed cases when disease was suspected clinically or by imaging studies. [10][11][12] For MDD determination in the CSF, we used the detection of the mRNA of GD2 synthase as it was already reported 9 until it was replaced by CRX mRNA detection. 10 Specimens for MDD were blindly processed by the polymerase chain reaction operators.…”
Section: Mdd Evaluationmentioning
confidence: 99%